Hydrogel-Based Biomaterials Engineered from Natural-Derived Polysaccharides and Proteins for Hemostasis and Wound Healing - Cheng, Junyao; Liu, Jianheng; Li, Ming; Liu, Zhongyang; Wang, Xing; Zhang, Licheng; Wang, Zheng (Frontiers in Bioengineering and Biotechnology, 2021)
Rapid and effective hemostasis is of great importance to improve the quality of treatment and even save lives in emergency, surgical practice, civilian, and military settings. Traditional hemostatic materials such as tourniquets, gauze, bandages, and sponges have shown limited efficacy in the management of uncontrollable bleeding, resulting in widespread interest in the development of novel hemostatic materials and techniques. Benefiting from biocompatibility, degradability, injectability, tunable mechanical properties, and potential abilities to promote coagulation, wound healing, and anti-infection, hydrogel-based biomaterials, especially those on the basis of natural polysaccharides and proteins, have been increasingly explored in preclinical studies over the past few years. Despite the exciting research progress and initial commercial development of several hemostatic hydrogels, there is still a significant distance from the desired hemostatic effect applicable to clinical treatment. In this review, after elucidating the process of biological hemostasis, the latest progress of hydrogel biomaterials engineered from natural polysaccharides and proteins for hemostasis is discussed on the basis of comprehensive literature review. We have focused on the preparation strategies, physicochemical properties, hemostatic and wound-healing abilities of these novel biomaterials, and highlighted the challenges that needed to be addressed to achieve the transformation of laboratory research into clinical practice, and finally presented future research directions in this area.